2002
DOI: 10.1200/jco.2002.20.4.1026
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Systemic and Intratumoral Effects of Tamoxifen and the Aromatase Inhibitor Vorozole in Postmenopausal Patients With Primary Breast Cancer

Abstract: The correlation with vorozole of Ki67 with volume and clinical response supports this as an intermediate marker. The nonsignificant effects on bone and lipid metabolism by the aromatase inhibitor may be important to consider for adjuvant and potential prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
28
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 39 publications
6
28
1
Order By: Relevance
“…The same group have also presented results from a randomised neoadjuvant trial comparing the aromatase inhibitor vorozole with tamoxifen. Ki67 levels fell within 2 weeks of treatment and remained suppressed at surgery 3 months later (Harper-Wynne et al, 2002). These effects are therefore apparent before evidence of morphological changes in tumour pathology and clinical evidence of changes in tumour volume.…”
Section: Discussionmentioning
confidence: 84%
“…The same group have also presented results from a randomised neoadjuvant trial comparing the aromatase inhibitor vorozole with tamoxifen. Ki67 levels fell within 2 weeks of treatment and remained suppressed at surgery 3 months later (Harper-Wynne et al, 2002). These effects are therefore apparent before evidence of morphological changes in tumour pathology and clinical evidence of changes in tumour volume.…”
Section: Discussionmentioning
confidence: 84%
“…In OR-positive IBC, changes in cellular proliferation measured by Ki67 nuclear antigen labelling can be used to reliably predict the response to antioestrogen therapy (Clarke et al, 1993;Chang et al, 2000;Dowsett et al, 2001a;Robertson et al, 2001;Harper-Wynne et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of patients with IBC have shown that early changes (o3 weeks) in cell proliferative indices and PR expression occur after antioestrogen therapy (Clarke et al, 1993;Chang et al, 2000;Dowsett et al, 2001a;Robertson et al, 2001;Harper-Wynne et al, 2002) in OR-positive (but not OR-negative) tumours and these changes are accepted as surrogate markers of clinical tumour response, with tamoxifen treatment increasing (Chang et al, 2000;Robertson et al, 2001) and aromatase inhibitor therapy decreasing PR expression .…”
mentioning
confidence: 99%
“…Data from relatively small studies supported the possibility that biomarkers may predict tumor response to chemotherapy (Chang et al 2000). In a neoadjuvant endocrine therapy trial, the aromatase inhibitor vorozole was compared with tamoxifen, and after 2 weeks it showed a greater fall in Ki-67 (58% vs 43%, respectively) that was weakly associated with clinical response at 12 weeks (Harper-Wynne et al 2002). In the recently reported IMPACT trial, the neoadjuvant use of tamoxifen versus the third-generation aromatase inhibitor anastrozole versus the combination was compared in 330 postmenopausal patients with primary ER-positive breast cancer (Dowsett et al 2005).…”
Section: Presurgical Biomarker Studies Of Endocrine/sti Therapymentioning
confidence: 99%